2017
DOI: 10.1007/s10853-016-0511-6
|View full text |Cite
|
Sign up to set email alerts
|

Sandwiched epoxy–alumina composites with synergistically enhanced thermal conductivity and breakdown strength

Abstract: Development of polymer-based composites with simultaneously high thermal conductivity and breakdown strength has attracted considerable attentions owing to their important applications in both electronic and electric industries. In this study, we successfully design novel epoxy-based composites with nanoAl 2 O 3 /epoxy composite layer sandwiched between micro-Al 2 O 3 /epoxy composite layers, which show synergistically and significantly enhanced thermal conductivity and breakdown strength. Compared with the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…As thermally conductive fillers, AlN, Al 2 O 3 , hexagonal-BN, carbon nanotubes and graphene have been often investigated to increase the thermal conductivity of polymer matrix. [9][10][11][12] Zhao et al investigated the effect of (3-mercaptopropyl)trimethoxysilane (MPTS)and copper-coated carbon fiber (M-Cu-CF) on thermal conductivity of the silicone rubber composites. It was found that the thermal conductivity of the M-Cu-CF/SR composites reached 1.99 W m −1 K) −1 with only 4.0 wt% filler loading.…”
Section: Introductionmentioning
confidence: 99%
“…As thermally conductive fillers, AlN, Al 2 O 3 , hexagonal-BN, carbon nanotubes and graphene have been often investigated to increase the thermal conductivity of polymer matrix. [9][10][11][12] Zhao et al investigated the effect of (3-mercaptopropyl)trimethoxysilane (MPTS)and copper-coated carbon fiber (M-Cu-CF) on thermal conductivity of the silicone rubber composites. It was found that the thermal conductivity of the M-Cu-CF/SR composites reached 1.99 W m −1 K) −1 with only 4.0 wt% filler loading.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, to achieve a better performance, the tendency in electronic technology has been towards integrating more transistors into a single chip. Yet this has caused the escalation of energy dissipation and significant heat fluxes in a device, which negatively influences its lifetime and reliability [ 1 , 2 , 3 , 4 , 5 ]. So, novel materials with better electrical and thermal performance are needed.…”
Section: Introductionmentioning
confidence: 99%
“…To improve thermal conductivity of epoxy resin, the fillers of micro-scale with high thermal conductivity can be considered. Nevertheless, the dilemma for using micro-sized inorganic particles is that the increase of thermal conductivity is usually attained at the expense of a significant decrease in breakdown strength, which thus limits their applications in high output electrical devices [ 2 , 10 , 11 ]. Thus, it can be seen that the development of epoxy-based composites with high thermal conductivity and dielectric breakdown strength is impending.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent bonds can enhance the adherence between nanoparticles and polymers. A great deal of studies demonstrated that modified nanoparticles could decrease agglomeration of the nanoparticles and enhance their interfacial bonding in polymer matrix and organic solvent . Salimi et al.…”
Section: Introductionmentioning
confidence: 99%